2012
DOI: 10.1002/aenm.201200337
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Used Nd‐Fe‐B Sintered Magnets via a Hydrogen‐Based Route to Produce Anisotropic, Resin Bonded Magnets

Abstract: Hydrogen processing (HD + HDDR) is used to recycle Nd‐Fe‐B sintered magnets yielding anisotropic resin bonded magnets (RBM). HD produces single‐crystalline powders from the sintered magnets. HDDR improves the magnetic properties by producing ultrafine grained, highly textured polycrystals. RBM produced from optimally processed recycled material shows comparable magnetic properties to non‐recycled RBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 30 publications
0
38
0
1
Order By: Relevance
“…This demonstrates the suitability of powders derived from sintered magnets for anisotropic magnet development, as has been suggested by others. 11 Fig . 4 shows the verification of the uniformity in the magnetic properties of the extruded filament.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates the suitability of powders derived from sintered magnets for anisotropic magnet development, as has been suggested by others. 11 Fig . 4 shows the verification of the uniformity in the magnetic properties of the extruded filament.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [46,78,79] studied the influence of particle distribution and hydrogenation conditions, and found that (1) the oxygen content decreases rapidly as particle size distribution increases and (2) higher H 2 pressure during hydrogenation results in decreasing oxygen content. Both Sheridan et al [80] and Gutfleisch et al [81] used a higher processing pressure during disproportionation and avoided subsequent oxygen exposure by performing both the v-HD and s-DR processes in the same furnace. They showed that anisotropic resin-bonded magnets could be produced by recycling Nd-Fe-B sintered magnets using a combined d-HDDR (dynamic HDDR) route.…”
Section: Recycling Via Hydrogenationmentioning
confidence: 99%
“…The separation and production of RE metal using electrolysis was first studied by Kobayashi et al [52,80,81] using molten fluoride (LiF-CaF 2 -NdF 3 ) and an iron group (RE-IG) alloy diaphragm. Waste containing RE was used as the anode, and REs were anodically dissolved by molten salt electrolysis as shown in Fig.…”
Section: Electrolysis Using Molten Salt and Ionic Liquidsmentioning
confidence: 99%
“…Kwon [5] studied on recycling sintered magnet scrap to prepare bonded magnet powders by adding several rare earth oxide and fluoride after HD process. Gutfleisch [6] showed that anisotropic resin bonded magnets could be produced by recycling Nd-Fe-B sintered magnets using a combined HD and d-HDDR route. Périgo [7] employed the HDDR process to recycle N42 sintered magnets for isotropic powders.…”
Section: Introductionmentioning
confidence: 99%